Quantum field theory : a diagrammatic approach - Kleiss, Ronald (Cambridge: Cambridge University Press, 2021)
"Let us first consider a general Hamiltonian of Z electrons moving around a nucleus that contains the Coulomb interaction, the spin-orbit coupling, and the hyperfine coupling. These are the three effects that determine the electronic structure of an atom. Here we should emphasize the important role of the separation of energy scales; that is to say, the typical energy scales of these three terms are quite different. Thanks to the separation of energy scales, we can analyze them one by one, which enables us to obtain a clear picture of the electron structure"--
Includes bibliographical references and index.
Keywords: Quantum field theory